Vocal Cord Dysfunction: A Frequently Forgotten Entity - S. Campainha; C. Ribeiro; M. Guimarães; R. Lima (Case Reports in Pulmonology)
Vocal cord dysfunction (VCD) is a disorder characterized by unintentional paradoxical adduction of the vocal cords, resulting in episodic shortness of breath, wheezing and stridor. Due to its clinical presentation, this entity is frequently mistaken for asthma. The diagnosis of VCD is made by direct observation of the upper airway by rhinolaryngoscopy, but due to the variable nature of this disorder the diagnosis can sometimes be challenging. We report the case of a 41-year old female referred to our Allergology clinics with the diagnosis of asthma. Thorough investigation revealed VCD as the cause of symptoms.